Cementing does not increase the immediate postoperative risk of death after total hip arthroplasty or hemiarthroplasty: a hospital-based study of 10, 677 patients. (4th May 2019) - Ekman, Elina; Laaksonen, Inari; Isotalo, Kari; Liukas, Antti; Vahlberg, Tero; Mäkelä, Keijo
Abstract : Background and purpose — It has been suggested that cemented arthroplasty is associated with increased peri- and postoperative mortality due to bone cement implanting syndrome, especially in fracture surgery. We investigated such an association in elective total hip arthroplasty (THA) patients and hemiarthroplasty (HA) patients treated for femoral neck fracture. Patients and methods — All 10, 677 patients receiving elective THA or HA for fracture in our hospital between 2004 and 2015 were identified. Mortality rates for cemented and uncemented THA and HA were compared at different times postoperatively using logistic regression analysis. Analysis was adjusted for age, sex, ASA class, and year of surgery. Results — Adjusted 10- and 30-day mortality after cemented THA was comparable to that of the uncemented THA (OR 1.7; 95% CI 0.3–8.7 and OR 1.6; CI 0.7–3.6, respectively). There was no statistically significant difference in the adjusted 2-day mortality in the cemented HA group when compared with the uncemented group. However, in a subgroup analyses of ASA-class IV HA patients there was a difference, statistically not significant, during the first 2 days postoperatively in the cemented HA group compared with the uncemented HA group (OR 2.1; CI 0.9–4.7). Interpretation — Cementing may still be a safe option in both elective and hip fracture arthroplasty. Excess mortality of cemented THA and HA in the longer term is comorbidity related, not due to bone cement implantation syndrome. However, in the most fragile HA patient group caution is needed at the moment of cementing.